Edukasi Etika Batuk yang Benar sebagai Upaya Preventif Penularan Tuberkulosis - Yusuf Hanafiah; Linawati Togatorop; Yuni Siharnida Lubis (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Tuberculosis remains a health problem, especially in developing countries including Indonesia. The purpose of this community service activity is to increase public knowledge about proper coughing etiquette as an effort to prevent pulmonary TB. The implementation method includes lectures and role play. The target is 103 residents of Hamlet 1, Tanjung Anom Village. The results of this activity show that the level of knowledge about proper coughing etiquette after education improved to sufficient knowledge in 61 people (48.8%), good knowledge in 22 people (28.0%), and insufficient knowledge in 20 people (23.2%). It is concluded that there was an increase in residents' knowledge after being educated on proper coughing etiquette.